Design of Robot Gripper Mechanism for ROBOCON Robot Competition - Alif Aiman bin Ahmad Othman, Alif Aiman (Universiti Teknologi Petronas, 2009)
The project is conducted by assumptions that are prototype built will consist of only lifter and gripper and cost for project research and prototype are neglected. Since there is no robot base and no movement of robot, the workpieces are feed into gripper jaw opening by external action. The outcome is development of an aluminum prototype model of a robot gripper.